Calculation method for internal force and deformation of the prestressed I-beam on the elastic foundation - Ye, Yangsheng; Wei, Shaowei; Cai, Degou; Yang, Jianmin; Wei, Peiyong; Yue, Cuihong; Wu, Shangrui (Frontiers in Earth Science, 2023)
The elastic foundation beam theory has been widely used in civil engineering, including railway, tunnel, and building foundation. With the development of fabricated structures, more elastic foundation beams need to be prestressed. In order to explore the frame foundation beam with fabricated anchor-cable in the slope reinforcement project, in this paper, prestress is applied to both ends of the beam. Then, according to calculation method of internal force and deformation of the beam under concentrated force and the equivalent load theory of the prestressed structure, three new methods: finite difference method (FDM) of Euler-Bernoulli beam on Winkler foundation, FDM of Euler-Bernoulli beam on Pasternak foundation and theoretical analytical solution of Timoshenko beam on Winkler foundation, are deduced to calculate internal force and deformation under the prestress and concentrated force respectively. Typical calculation parameters are selected for design and verification via the three new methods and GEO5 respectively. The results show that the calculated values of the three new methods are basically consistent with those calculated by GEO5 software, which verifies the feasibility of the three new methods.